(untitled) - Steger, Carsten (Weinheim, 2008)
This first up-to-date textbook for machine vision software provides all the details on the theory and practical use of the relevant algorithms. The first part covers image acquisition, including illumination, lenses, cameras, frame grabbers, and bus systems, while the second deals with the algorithms themselves. This includes data structures, image enhancement and transformations, segmentation, feature extraction, morphology, template matching, stereo reconstruction, and camera calibration. The final part concentrates on applications, and features real-world examples, example code with HALCON, and further exercises. Uniting the latest research results with an industrial approach, this textbook is ideal for students of electrical engineering, physics and informatics, electrical and mechanical engineers, as well as those working in the sensor, automation and optical industries. Free software available with registration code
Keywords: Computer vision,Computer algorithms,Thị lực máy tính,Thuật toán máy tính